JARINGAN KOMUNIKASI DALAM PENGELOLAAN DAN PENYEDIAAN INFORMASI PUBLIK (Studi Komunikasi Humas Pemerintah dan Satuan Kerja Perangkat Daerah Di Kota Solok) - Jhoni Trisno (Professional: Jurnal Komunikasi dan Administrasi Publik, 2018)
This study was conducted to describe the communication network in the management and provision of public information in Government Public Relations and Regional Work Unit (SKPD) in Solok City. The description of the communication network was obtained using descriptive qualitative research methods with data collection techniques of interview, observation and documentation. The communication network observed revolves around the functions of the communication network, connectivity, communication network typology, and separator of Solok City Public Relations Division and other Regional Work Units (SKPD). The results of the study illustrate that; 1) The function of the Government Public Relations communication network with other SKPD in the City of Solok as a technical person in charge of being able to manage the organization's internal communication. The Public Relations Department has provided information technology in the form of an application system in the form of integrated internet in each organizational unit, 2) Connectivity of the Public Relations Section of Solok City Regional Secretariat and other SKPD have strong and close connections because they use informal communication that prioritizes interpersonal closeness, the Public Relations and other SKPD departments in Solok City Government are running decentralized, 4) In the communication network of the Solok City Regional Secretariat and other SKPD, each member of each agency can communicate with each other, either directly or using media, such as telephones.